Miniaturization in Sample Preparation - Pena Pereira, Francisco (De Gruyter, 2014)
Miniaturization is a challenge thrown down to analytical chemistry. The replacement of conventional analytical systems by miniaturized alternatives during the last years is noticeable. Specifically, the miniaturization of traditional sample preparation techniques (e.g., solid-phase extraction or solvent extraction) led to the development of environmentally benign analytical methods. This book aims to provide an overview of the challenges and achievements inthe application of the miniaturized sample preparation methods in analytical laboratories. It includes both theoretical and practical aspects of miniaturized sample preparation approaches and hence should be of interest to researchers, students and teachers of analytical and bioanalytical chemistry, environmental sciences and environmental engineering.